PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN SEPEDA MOTOR HONDA SCOOPY DI KOTA TALUK KUANTAN - Rizky, Prayudi; Aida, Nursanti; Rendra, Wasnury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to determine the effect of Product Quality (X1) and Price (X2) on Purchase Decision (Y1) and Customer Satisfaction (Y2) Honda Scoopy Motorcycles at Taluk Kuantan. The population of study was customers who have Honda Scoopy automatic motorcycles at Taluk Kuantan whose numbers are not known with certainly. Sampling technique used was purposive sampling and 144 people were selected to be sampled. Path Analysis with software SPSS version 24 was used as methods of data analysis. The results were: 1) Product Quality had a positive and significant effect on Purchase Decision; 2) Price had a negative and significant effect on Purchase Decision; 3) Purchase Decision had a positive and significant effect on Customer Satisfaction; 4) Product Quality had a positive and significant effect on Customer Satisfaction throughwork Purchase Decision; 5) Price had a negative and significant effect on Customer Satisfaction throughwork Purchase Decision.Keyword: Product Quality, Price, Purchase Decision, Customer Satisfaction.